PENGARUH GAYA KEPEMIMPINAN DAN PENGAWASAN KERJA TERHADAP KINERJA KARYAWAN PADA KANTOR PERWAKILAN WILAYAH BANK INDONESIA PROVINSI SULAWESI SELATAN - Krisnanto, Budhi; Muchsidin, Feronica Fungky; Saeni, Nuraeni; Lawalata, Izaac L.D; Sari, Indah Permata (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2023)
Human resources are the main asset in the organization with the role of implementing policies and operational activities. Good work performance can provide optimal results for the organization, requiring good management to create a comfortable work environment. Two factors that influence employee performance in this study are leadership style and work supervision. Leadership style is identified as the first factor affecting performance, while supervision is identified as the second factor. Both contribute positively to improving employee performance, as found in previous studies. The purpose of the study was to analyze the effect of leadership style and work supervision on employee performance at Regional Representative Office of Bank Indonesia South Sulawesi. The analysis method in this study uses multiple linear regression regression using the help of SPSS version 23 software. The sample used amounted to 35 first line employees at the Regional Representative Office of Bank Indonesia of South Sulawesi Province. Representative Office of Bank Indonesia South Sulawesi Province.The results showed that there was an influence of leadership style and work supervision on leadership style and work supervision on employee performance at Regional Representative Office of Bank Indonesia of South Sulawesi Province. style leadership style has a positive and significant effect on employee performance as indicated by the regression coefficient of the leadership style variable variable regression coefficient of 0.222 which is positive and significant at 0,044. Work supervision has a positive and significant effect on employee performance as indicated by the variable regression coefficient work supervision variable regression coefficient of 0.577 which is positive and significant at 0.000. As well as leadership style and work supervision simultaneously have a positive and significant effect on employee performance as shown the probability value (sig) of 0.000 is smaller than 0.05